A Risk-Return Measure of Hedging Effectiveness: A Reply - Howard, Charles T.; D'Antonio, Louis J. (Journal of Financial and Quantitative Analysis, 1987)
In this reply, we point out that Chang and Shankar's measure of hedging performance, which they label HE1, is not an adequate measure. We describe an alternative measure, labeled HBS, which has a number of desirable ex ante and ex post statistical properties.